Niche breadth and overlap of spotted deer and domestic cattle with swamp deer in tropical region of Nepal - Siddhartha Regmi; Bijaya Neupane; Bijaya Dhami; Deepak Gautam; Saroj Panthi; Megharaj Poudel (Ecological Processes, 2022)
Abstract Background Knowledge about the niche overlap among wild species and domestic cattle is helpful to conserve and manage wildlife. We assessed the habitat niche breadth and overlap of sympatrically living spotted deer (Axis axis) and domestic cattle with swamp deer (Cervus duvaucelii) in Shuklaphanta National Park, Nepal during the dry season to explore the possibility of interspecific competition by studying the habitat use by these species. The assumption was made that the presence of pellets is proof of habitat used by species. Methods Grids of 2 km × 2 km have four subgrids, each with four sample plots, making a total of 16 plots (20 m × 20 m) in each grid. The size of each sub-grid was 200 m × 200 m and they were placed randomly inside the grid but at least 1 km apart from one another. The data was collected in a 96 plots in total. Levin’s niche breadth and Morisita’s overlap index were calculated to determine the niche breadth and the habitat overlap, respectively. Results The Levin’s measure of niche breadth suggested that spotted deer had the highest acclimatization with an index value of 0.94, followed by domestic cattle at 0.50, and swamp deer at 0.33 in our study area. Thus, our findings supported the evidence that spotted deer are habitat generalists, whereas swamp deer are habitat specialists. The swamp deer had lower niche breadth and more overlap with domestic cattle. Conclusion Our study showed the least niche breadth of swamp deer in comparison to spotted deer and domestic cattle. The domestic cattle had the highest and least niche overlap with spotted deer and swamp deer, respectively, in terms of habitat use. Our study suggests that domestic cattle grazing should be stopped, and grassland management should be carried out for the benefit of ungulates. Similar studies should be conducted, including different seasons and places, prior to appropriate habitat management. In addition, further studies are needed to quantify the extent of interspecific competition by incorporating more species.